Implementasi Brand Activation melalui Konser Musik untuk Membangun Minat Pengunjung PosBloc - Hinandra, Alvin Christian; Pandrianto, Nigar (Prologia, 2025)
Jakarta, with its long historical background, possesses numerous cultural heritages, including historical buildings such as PosBloc. PosBloc has transformed into a creative hub that integrates art, culture, and entertainment. One of its main strategies is utilizing music concerts as brand activation to attract visitors. This study aims to analyze the role of music concerts as a marketing communication tool in building visitor interest in PosBloc and its contribution to heritage preservation. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation studies involving visitors, organizers, and relevant practitioners. Analysis was conducted using source triangulation to ensure data validity. The findings indicate that music concerts at PosBloc enhance brand awareness, create emotional engagement, and strengthen visitor loyalty, particularly among younger generations. However, visitor numbers remain limited, and the effectiveness of marketing strategies needs improvement through social media and the integration of cultural elements. This study underscores the importance of cross-sector collaboration to optimize the social, economic, and cultural benefits of PosBloc. Jakarta, dengan usia sejarah panjang, memiliki banyak warisan budaya, termasuk bangunan bersejarah seperti PosBloc. PosBloc telah bertransformasi menjadi pusat ruang kreatif yang menggabungkan seni, budaya, dan hiburan. Salah satu strategi utamanya adalah menggunakan konser musik sebagai brand activation untuk menarik minat pengunjung. Penelitian ini bertujuan untuk menganalisis peran konser musik sebagai alat komunikasi pemasaran dalam membangun minat pengunjung PosBloc, serta kontribusinya terhadap pelestarian heritage. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data dikumpulkan melalui wawancara mendalam, observasi, dan studi dokumentasi dari pengunjung, penyelenggara, dan praktisi terkait. Analisis dilakukan menggunakan triangulasi sumber untuk memastikan validitas data. Hasil penelitian menunjukkan bahwa konser musik di PosBloc meningkatkan kesadaran merek, menciptakan keterlibatan emosional, dan memperkuat loyalitas pengunjung, terutama generasi muda. Namun, jumlah pengunjung masih terbatas, dan efektivitas strategi pemasaran perlu ditingkatkan melalui media sosial dan integrasi elemen budaya. Penelitian ini menegaskan pentingnya kolaborasi lintas sektor untuk mengoptimalkan manfaat sosial, ekonomi, dan kultural PosBloc.